The "Provoked Husband or, A Journey to London a Comedy - Vanbrugh, John, 1664-1726. (London : Company, 1825)
Theatre, last night. For the benefit of Mrs. Gilfert. This evening, Friday, April 22nd, 1825, will be acted, the admired comedy of "The Provoked Husband, or, A Journey to London" ... end of the play, an entire new pas seul, by Mrs. Neuville after which Mr. Hunter will (by particular desire) perform a variety of new and wonderful performances on the tight rope. To conclude with (for the first time these many years) the grand melo-drama, called "The Miller and his Men" ...
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Comedy; Playbills -- South Carolina -- Charleston; Playbills -- 1825.